Research progress of porcine epidemic diarrhea virus S protein - Luo, Haojian; Liang, Zhaoping; Lin, Junjie; Wang, Yiqiao; Liu, Yingying; Mei, Kun; Zhao, Mengmeng; Huang, Shujian (Frontiers in Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) is a single-stranded RNA virus with a capsid membrane that causes acute infectious gastrointestinal disease characterized by vomiting, diarrhea, and dehydration in swine. Piglets are more susceptible to PEDV than adults, with an infection rate reaching 90% and a fatality rate as high as 100%. Moreover, PEDV has a rapid transmission rate and broad transmission range. Consequently, PEDV has caused considerable economic losses and negatively impacted the sustainability of the pig industry. The surface spike (S) glycoprotein is the largest structural protein in PEDV virions and is closely associated with host cell fusion and virus invasion. As such, the S protein is an important target for vaccine development. In this article, we review the genetic variation, immunity, apoptosis-induction function, virulence, vaccine potential, and other aspects of the PEDV S protein. This review provides a theoretical foundation for preventing and controlling PEDV infection and serves as a valuable resource for further research and development of PEDV vaccines.PEDV was first identified in China in the 1980s and a subsequent outbreak occurred in the United States in 2013. Until 1984, PEDV was identified in confirmed cases of PED using fluorescence-